POSITIONAL PERFORMANCE DIFFERENCES IN U14 ELITE LEAGUE FOOTBALL PLAYERS - Vicol Sebastian-Iulian; Teodorescu Silvia (Sport şi Societate, 2025)
monitoring systems such as Catapult and Polar providing coaching staff with objective data on player performance. These tools enhance both training effectiveness and match analysis. This study aims to analyze the performance metrics recorded by the U14 football team of Dinamo Bucharest Academy, who were monitored using the Catapult system during 15 matches in the U14 Elite League. The objective was to determine whether significant differences exist in key performance indicators—total distance covered, distance covered per minute, maximum speed, and distance covered across different speed zones—based on playing position (defenders, midfielders, forwards). Data analysis focused exclusively on the first half of matches (35 minutes). The team utilized a 4-3-3 formation, and matches were played on a 70m x 60m field with standard 11-a-side goals. The results indicate that midfielders covered significantly greater distances than defenders and forwards, both in total distance and distance per minute. Forwards recorded the highest maximum speed, which was 11% greater than that of midfielders and 8% greater than that of defenders. Additionally, forwards covered the most distance in high-speed zones, whereas midfielders were dominant in moderate-speed zones. These findings highlight the positional demands of youth football, emphasizing the need for position-specific training programs.